Representasi Androgini Jovi Adhiguna di Video Blog YouTube - Chela Merchela Funay; Lintang Ratri Rahmiaji (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
Jovi Adhiguna’s vlog is one of the social media accounts on YouTube featuring the personal life of a Jovi Adhiguna with his uniqueness as an androgyny. Androgyny is an individual who has two gender roles with masculine and feminine social values that are equally strong and emerge at the same time. This study aims to find out how the androgynous representation through semiotic analysis and also to see the effect of androgyny on the dominant ideology of heteronativity. In analyzing the three vlogs of Jovi, the author uses the theory of semiotics from Roland Barthes, which in theory is expressed in the meaning system of denotation, connotation, and myth. Based on the results of three vlogs Jovi's research, shows the representation that androgyny is not a gender identity that has a sexual orientation but the development of gender roles, in which the masculine self is integrated into the feminine traits. Nevertheless, Jovi also represents androgyny as “the other”, the realization that he is the “self” outside the normal conception prevailing in society, discriminated against because of the differences he believes in, while continuing to refuse to be called a “banci”, “waria”, “bencong”, and transgender. Other findings suggest that androgynous tend to engage in creative activities that are not limited by gender or unisex, but tend to feminine headlines such as fashion and beauty. Through the representation that appears on Jovi's vlogs, it shows that the androgyny concept that is presented is not fully against heteronativity and even tends to strengthen the ideology of heteronativity by recognizing the concept of androgyny as liyan.